Elucidation of aqueous alteration of Yamato 000749 based on multi-probe microscopy - Shiraishi, Naoki (2019)
The Tenth Symposium on Polar Science/Special session: [OA] Antarctic meteorites, Thur. 5 Dec. / 3F Multipurpose conference room, National Institute of Polar Research conference object